Factors Affecting Personal Attitude of Undergraduate Agricultural Students to Start a Business: The Moderating Role of Family Business Status - Mavhungu, Mbulaheni Lordwin (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
This study investigates the relationship between access to resources, subjective norms sociocultural forces; and the personal attitude of undergraduate agricultural students towards establishing a business. This relationship was looked at from a family-business status viewpoint. Data was collected from students of the six universities in South Africa registered for various agricultural programmes. Data analysis was computed using SPSS version 29. The study confirmed that subjective norms and sociocultural forces predict personal attitude towards starting a business, but not access to resources. The moderating role of family business status was not statistically significant for all factors. However, undergraduate agricultural students' access to resources and family business status relationships from families not owning a business were statistically significant. A significant relationship was also found between subjective norms and the family business status of agricultural students. The entrepreneurial syllabus should expose students to these extrinsic factors, as this shapes their attitude towards engaging in entrepreneurship. A positive personal attitude will likely lead to business establishment. Farming and entrepreneurship can address youth unemployment, employment creation, economic growth, and fighting poverty. Entrepreneurship is influenced by access to resources; however, agricultural students aren't finding it significant. Therefore, entrepreneurial education is essential for students to gain knowledge of this important business start-up factor.